G44(P) Bioelectric impedance vector analysis (biva) and clinical outcome in hospitalised children. (12th March 2018) - Roche, S; Lara-Pompa, NE; Macdonald, S; Fawbert, K; Valente, JE; Hill, S; Wells, JCK; Fewtrell, MS
Abstract : Aims: Bioelectric impedance analysis (BIA) is a widely used, simple bedside technique, but clinical use is limited by the need to convert raw measurements to body composition, using equations that are potentially inappropriate. The use of the raw bioelectric impedance vectors (BIV), resistance (R), reactance (Xc) and phase angle (PA) – suggested to indicate body fluid, cell mass and cell health respectively – may be an alternative for monitoring disease progression/treatment. However, clinical experience of BIV in children is limited and previous studies have not standardised for age. We investigated predictors of BIV and their ability to predict clinical outcomes in children with complex diagnoses admitted to a children's hospital. Methods: R, Xc and PA were measured using BODYSTAT Quadscan 4000 on admission in 70 children aged 4.6–16.8 years (mean 10.0). R and Xc were indexed by height (H) and BIVSDS generated for age and sex using data from healthy children. Potential predictors (activity, wheelchair use, steroid treatment, enteral/parenteral nutrition); and clinical outcomes (greater-than-expected length-of-stay (LOS), complications (unplanned transfer to ICU, increased artificial nutrition, infection requiring antibiotics)) were recorded at discharge. Results: Mean R/HSDS was significantly higher (0.99 (SD 1.32)) and PASDS significantly lower (−1.22 (1.51)) than the population mean, with a wide range for all BIVSDS. No significant predictors of BIVSDS were identified. BIVSDS were not significantly different in patients with or without adverse outcomes although R/HSDS was higher in children with increased LOS (mean difference mean difference 0.42 (95% CI=−0.26 to −1.11) or complications (mean difference 0.49 (95% CI −0.34 to 1.33). Conclusion: This group of complex patients had abnormal mean BIVSDS suggestive of reduced hydration and poor cell health. However, factors considered as clinical predictors showed no significant association, and BIVSDS were not significantly related to clinical outcomes; possibly reflecting the necessary use of generic predictors and outcomes in this heterogeneous population. Children with adverse outcomes showed a trend towards higher R/HSDS, suggesting lower hydration. Further investigation in specific patient groups, including those with acute fluid shifts and using disease-specific outcomes, may help to better define the clinical role of BIV.